SAR of a new antischistosomal urea carboxylic acid. Issue 23 (15th December 2018) - Wu, Jianbo; Wang, Chunkai; Häberli, Cécile; White, Karen L.; Shackleford, David M.; Chen, Gong; Dong, Yuxiang; Charman, Susan A.; Keiser, Jennifer; Vennerstrom, Jonathan L.
Graphical abstract: Highlights: Urea carboxylic acids, a new antischistosomal chemotype. Baseline structure–activity relationship (SAR). Analogs were quite polar, had high aqueous solubility, and were metabolically stable. Modifications to the gem -dimethyl and urea functional group were tolerated. Abstract: Urea carboxylic acids, products of aryl hydantoin hydrolysis, were recently identified as a new antischistosomal chemotype. We now describe a baseline structure–activity relationship (SAR) for this compound series. With one exception, analogs of lead urea carboxylic acid2 were quite polar with Log D7.4 values ranging from −1.9 to 1.8, had high aqueous solubilities in the range of 25–100 µg/mL, and were metabolically stable. None of the compounds had measurable in vitro antischistosomal activity or cytotoxicity, but four of these had moderate worm burden reduction (WBR) values of 42–70% when they were administered as single 100 mg/kg oral doses to S. mansoni -infected mice. These data indicate that with the exception of the gem -dimethyl substructure and the distal nitrogen atom of the urea functional group, the rest of the structure of2 is required for in vivo antischistosomal activity.